Method and device for detection of insulation breakdown on hull in power circuits of locomotives - A. N. Kalyakulin (Омский научный вестник)
One of the significant problems of modern locomotives is to ensure their electrical and fire safety. A method is described that allows to quickly determine the number of the traction motor in the power circuit, the state of isolation of which is emergency. The disadvantage of the existing protection method is that it only provides information about the loss of insulation integrity in the positive or negative circuit. The proposed method is based on the use of changes in electrical capacitance and insulation resistance in the circuit. The results of mathematical modeling and experimental research confirm the possibility of practical application of the breakdown detection device built on the basis of this method. In the course of the experiments, insulation breakdowns in the power circuit are successfully localized and emergency devices to be replaced are found.